Testing the aerobic stability of silage-based mixed rations using a multiple indicator approach - Martens, Siriwan; Jilg, Annette; Schneider, Mariana; Misthilger, Barbara; Ohl, Susanne; Steinhöfel, Olaf (Agricultural and Food Science, 2022)
Total Mixed Rations (TMR) including silages are commonly fed to cattle in many parts of the world, but they tend to deteriorate on exposure to air, especially in the warm season. The aim of the study was to develop an easy to implement protocol in order to compare the aerobic stability of different feed mixtures for lactating dairy cattle and to test the potential of TMR stabilizing products to delay spoilage. The experimental conditions were standardized to 25 °C ambient, and the sample dry matter was adjusted to 400 g kg-1 to challenge shelf life. Temperature rise in an insulated vessel, which is frequently used when testing silages, was shown to be one promising indicator of spoilage activity. Furthermore, determination of pH, scores for visual occurrence of yeasts and moulds and condensation from 0–4 were successfully applied at the end of the 72 h period. A dosage of 4.5 l propionic acid t-1 proved suitable as a positive control when compared to 1.5 and 3.0 l t-1. The commercial products tested at the recommended dose had a similar efficacy. The stabilizing effect depended principally on the original hygienic condition of the ration. Visual evaluation plus the recording of pH, in addition to continuous temperature measurement facilitated this appraisal. Early signs of spoilage, in particular, can only be assessed by visual appraisal. Thus, an evaluation of a combination of indicators of aerobic stability is recommended.